A Novel Tracer Technique to Quantify the Lithogenic Input Flux of Trace Elements to Qinghai Lake - Zhang, Pu; Pei, Xuezheng; Cao, Chenyang; Chen, Chi; Gong, Ziqin; Li, Xuerou; Pang, Jingya; Liang, Lihua; Li, Xiangzhong; Ning, Youfeng; Edwards, R.Lawrence (Frontiers in Earth Science, 2022)
Thorium (Th) isotopes were applied to quantify the contributions of lithogenic inputs to the Qinghai Lake (QHH). Concentrations of dissolved 232Th and 230Th were measured in 59 water samples collected from Qinghai Lake and its exogenous recharge rivers. There are significant differences in the concentration of 232Th of the sampled water in QHH that confirm the input of variable lithogenic material sources. The 230Th concentrations were used to calculate a scavenging residence time for Th, which was then applied to calculate the flux of dissolved 232Th by matching the measured concentrations of dissolved 232Th. Then the 232Th content of lithogenic material was used with the solubility of Th from the preliminary particle data from the Qinghai-Qaidam district. When using a Th solubility from particles of 1%, the fluxes of lithogenic material ranges from 0.03 to 59.30 g/m2/yr in the surface water, consistent with the flux results of settled particles from the previous study. When a large number of exogenous recharge rivers are mixed into the northwest basin of Qinghai Lake, the 232Th content and lithogenic flux of the lake water are mainly influenced by the type and content of the particles in the Buha and Shaliu rivers. Conversely, in south basin with limited recharging river, the 232Th content of the lake water away from the estuary is mainly influenced by the atmospheric dust. Further, based on 230Th normalization method (combining with 232Th and τTh), the Buha and Shaliu rivers located in the northwest basin contribute about 90% of the detrital flux to the lake. The lithogenic flux in the southeast lake is dominated by dust flux with a value of ~0.109 g/m2/yr, while the higher lithogenic flux at the bottom of the lake was likely generated by accumulated sinking particulate matter and resuspension of bottom sediments in September. This study confirms the utility of long-lived Th isotopes to quantify lithogenic inputs based on Th content of the dissolved lake water, and also supply deposition resolution information for QHH sediment records in some certainty.